RE-DESIGN UI/UX APLIKASI PNM DIGI KARYAWAN DENGAN METODE DESIGN THINKING UNTUK MENINGKATKAN KEPUASAN PENGALAMAN PENGGUNA - Fauzansyah, Ananda (UI Scholars Hub, 2024)
In the era of rapid technological advancement, the implementation of digital innovation has become a key factor in enhancing employee productivity ef iciency. The development of information technology provides opportunities for companies to optimize the use of electronic-based applications, such as the PNM Digi Employee Application. Therefore, this research aims to respond to and address the demands of technological changes by redesigning the UI/UX using the Design Thinking method. In the Define stage, three main problems requiring new design solutions were identified. Testing was conducted with five respondents through usability testing, followed by usability assessment using the System Usability Scale technique. The evaluation results showed a score of 80.5, indicating that the redesign of the PNM Digi Employee application using the Design Thinking method was successful in providing ef ective solutions to the existing problems. This new design not only improves the application's appearance but also makes users comfortable in using it.